Registration of four rice germplasm lines with improved resistance to sheath blight and blast disease - Jia, Y; Liu, G; Correa Victoria, Fernando J.; McClung, AM; Oard, J.H.; Jia, MH; Corell, JC (Wiley, 2012)
Rice sheath blight (ShB) and blast caused by the fungal pathogens Rhizoctonia solani Kühn and Magnaporthe oryzae B.C. Couch, respectively, are the two most serious diseases of rice worldwide. Four rice (Oryza sativa L.) germplasm lines, designated as LJRIL103 (Reg. No. GP‐140, PI 660982), LJRIL158 (Reg. No. GP‐141, PI 660983), LJRIL186 (Reg. No. GP‐142, PI 660984), and LJRIL220 (Reg. No. GP‐143, PI 660985), were selected from among 256 recombinant inbred lines (RILs) derived from a cross of the U.S.‐adapted cultivars ‘Lemont’ (PI 475833) and ‘Jasmine 85’ (PI 595927). These Lemont–Jasmine (LJ) RILs were officially released by the USDA‐ARS and the University of Arkansas Agricultural Experimental Station in cooperation with the International Center for Tropical Agriculture (CIAT), Colombia, and Louisiana State University, Baton Rouge, LA. These four RILs have resistance to ShB as determined in two greenhouse chamber assays and in inoculated field trials conducted in Stuttgart, AR; Beaumont, TX; and Crowley, LA in 2008 and 2009. They are also resistant to some blast races as determined in inoculated greenhouse tests. These LJ RILs contain most of the ShB quantitative trait loci (QTLs) identified on chromosomes 1, 2, 3, 5, 6, and 9 and blast QTLs identified on chromosomes 8, 9, 11, and 12 originating from the parents Jasmine 85 and Lemont. These four LJ RILs have agronomic and grain‐quality characteristics comparable with those of both parents. These LJ RILs can be used in rice‐breeding programs for pyramiding both ShB and blast resistance genes.